Short and Long-Run Labor Market Effects of Developing Country Exports: Evidence from Bangladesh - Raymond Robertson; Deeksha Kokas; Diego Cardozo; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2020)
This paper studies how a positive export shock - the sharp increase in garment-sector exports that began at the end of the Multifibre Arrangement (MFA) - spread through Bangladesh's labor markets. Although the end of the MFA was arguably exogenous to Bangladesh, we instrument export demand with OECD imports to ensure identification. We compare estimates of the local labor market effects (wages and informality) and estimates from wage equations that reflect the predictions from long-run, general-equilibrium neoclassical trade theory. As in other studies, we find that the export shock was localized both in terms of sector and geography. Wages increased and informality decreased in sub-districts more exposed to the export shock. Unlike in other studies, these local labor market effects dissipate quickly. Furthermore, Bangladesh's export shock was sector specific, limited predominantly to the female-intensive garment and textile sector. We show that, following the increase in exports of the female-intensive good, the male-female wage gap closes considerably throughout the country – not just in the apparel sector. In relatively small Bangladesh, the national labor market seems to be more integrated compared to larger countries studied, possibly suggesting that labor adjustment costs are lower in smaller countries.
Keywords: F13; F14; F15; F16; J23; J31; O15; O19; 330; local labor markets; Bangladesh; apparel; exports; wage inequality; Stolper-Samuelson